Outsider art and art therapy : shared histories, current issues and future identities - Cohen, Rachel (Online access with DDA: Askews (Medicine), 2017)
This book explores the intersection of outsider art, traditionally the work of psychiatric patients, offenders and minority groups, and art therapy. It focuses on their shared histories of art created in psychiatric care in order to help to clarify how each field is defined and identified today.